Study on fabric-based triboelectric nanogenerator using graphene oxide/porous PDMS as a compound friction layer. (February 2022) - Yang, Chii-Rong; Ko, Chi-Tse; Chang, Shu-Fang; Huang, Mao-Jung
Abstract: This study combined the commercially available conductive fabric with the polydimethylsiloxane (PDMS) layer containing graphene oxide (GO) to implement a fabric-based triboelectric nanogenerator (TENG) which is characterized by a simple process, low cost, high flexibility, and high stability. The findings showed that when the TENG used GO@PDMS compound layer, and after the surface was modified by SF6 plasma, the optimal open-circuit voltage of 140.4 V and short-circuit current of 2.57 μA were obtained. When the load resistance was 50 MΩ, the maximum power was 130.5 μW. Further testing illustrated this device to have excellent washability and tested for durability. When the TENG device was integrated with clothing and body, the action information could be obtained. This indicates that this device could be used as a posture or pressure sensor. As the TENG device can lighten up 180 green LEDs connected in series, it is suitably applied to develop microgenerators. Finally, this TENG device transmits signals to the mobile phone through a Bluetooth wireless module for a real-time display. It was proved the proposed fabric-based TENG sensor with self-powered and wireless transmission function has massive potential in future applications for use in wearable fitness trackers, E-skin of robotic arms, human–machine interfaces, and flexible touch sensors. Graphical Abstract: ga1 Highlights: A novel-based fabric TENG with advantages of simple process, washable, and high stability. The TENG performance with open-circuit voltage of 140.4 V, short-circuit current of 2.57 μA and maximum power of 130.5 μW. The TNEG was applied to four positions on the human body for sensing the movement. One hundred and eighty green LEDs were lighted up. The real-time TENG signals were displayed on the mobile phone through Bluetooth wireless module.